Initial Design of Forging Measuring Instrument for Application of Friction Welding - Bagus Muhammad Fauzi; Irza Sukmana; Yanuar Burhanuddin (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2020)
Friction welding is a metal joining technique without melting beforehand in which the process is to combine the rotation rate in one of the work materials. In the previous studies, the forging pressure parameters used for friction welding did not have a definite reference to the strength of the joint in friction welding. This project is to make initial design of forging measuring instrument for application of friction welding. The steps include conceptual design, embodiment process, and performance analysis. The conceptual design result includes hollow iron U-shape, telescopic iron, and telescopic iron with screw. The measuring system uses a 500 kg load cell, Arduino Leonardo, HX711amplifier, and data logger. Then, after all components are assembled, the load cell calibration is performed to determine the calibration factor. The next stage is to do pressure test to see the performance of forging measuring instrument of friction welding.